Essential oil content and composition of Indian Sandalwood (Santalaum album) in Sri Lanka - Subasinghe, U.; Gamage, M.; Hettiarachchi, Dhanushka (Dongbei Linye Daxue, 2013)
Santalum album (Indian Sandalwood) is found in the mountainous regions of the intermediate zone of Sri Lanka. Few studies have been conducted on sandalwood ecology in this region, and ours is the first recorded study of essential oil content and chemical composition of heartwood. We harvested two trees with State permission and took cross-sections for analysis. We demonstrated a difference in the heartwood formation and oil yield of the trees. The composition of the oil was found to be consistent between trees and along the trunk of the tree. Main aromatic compounds were santalols and other compounds are recorded in lesser quantities. Results of this study comply with the other published work on sandalwood elsewhere. This initial study on S. album in Sri Lanka provided promising results for the future of sandalwood agroforestry.